Respostas

2013-10-16T18:16:13-03:00
A) 12y + 5 = 2y + 8
    12y - 2 y = 8 - 5
      10 y = 3
          y = 3/10

 b)  5 (  3 -  x) + 2 ( x + 1) = x + 5
       15 - 5x + 2x + 2 = x + 5
         -5x + 2x - x = 5 -2 -15
           -6x +2x = 5 - 17
              - 4x = - 12      x(-1)
                  4x = 12
                     x = 12/4
                       X = 3

C) 5X + 20 ( 1 - X) = 5
     5X +  20 - 20x = 5
      5x -20x = 5 -20
       - 15x = - 15       x(-1)
          15x = 15
              x = 15/15
               x= 1
 

      
3 3 3